A randomized physiotherapy trial in patients with fecal incontinence: design of the PhysioFIT-study - de Bie Rob A; Hendriks Erik JM; Berghmans Bary CM; Bols Esther MJ; Melenhorst Jarno; van Gemert Wim G; Baeten Cor GMI (BMC, 2007)
Abstract Background Fecal incontinence (FI) is defined as the recurrent involuntary excretion of feces in inappropriate places or at inappropriate times. It is a major and highly embarrassing health care problem which affects about 2 to 24% of the adult population. The prevalence increases with age in both men and women. Physiotherapy interventions are often considered a first-line approach due to its safe and non-invasive nature when dietary and pharmaceutical treatment fails or in addition to this treatment regime. Two physiotherapy interventions, rectal balloon training (RBT) and pelvic floor muscle training (PFMT) are widely used in the management of FI. However, their effectiveness remains uncertain since well-designed trials on the effectiveness of RBT and PFMT versus PFMT alone in FI have never been published. Methods/Design A two-armed randomized controlled clinical trial will be conducted. One hundred and six patients are randomized to receive either PFMT combined with RBT or PFMT alone. Physicians in the University Hospital Maastricht include eligible participants. Inclusion criteria are (1) adults (aged ≥ 18 years), (2) with fecal incontinence complaints due to different etiologies persisting for at least six months, (3) having a Vaizey incontinence score of at least 12, (4) and failure of conservative treatment (including dietary adaptations and pharmacological agents). Baseline measurements consist of the Vaizey incontinence score, medical history, physical examination, medication use, anorectal manometry, rectal capacity measurement, anorectal sensation, anal endosonography, defecography, symptom diary, Fecal Incontinence Quality of Life scale (FIQL) and the PREFAB-score. Follow-up measurements are scheduled at three, six and 12 months after inclusion. Skilled and registered physiotherapists experienced in women's health perform physiotherapy treatment. Twelve sessions are administered during three months according to a standardized protocol. Discussion This section discusses the decision to publish a trial protocol, the actions taken to minimize bias and confounding in the design, explains the choice for two treatment groups, discusses the secondary goals of this study and indicates the impact of this trial on clinical practice. Trial registration The Netherlands Trial Register ISRCTN78640169.